2017
DOI: 10.4102/sajid.v32i1.67
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices in the control and prevention of malaria in four endemic provinces of Zambia

Abstract: This study sought to determine malaria knowledge levels, attitudes and practices of the communities in four malaria endemic provinces of Zambia. A cross-sectional survey on knowledge, attitude and practices (KAP) on malaria transmission, prevention and control was conducted among 584 household heads of randomly selected communities in Luapula, Lusaka, north-western and western provinces in Zambia. Data analysis was performed by both descriptive and inferential statistics. Knowledge levels in malaria with regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 3 publications
3
9
1
Order By: Relevance
“…Meanwhile, having at least secondary level of education was found associated with a positive in uence on malaria related attitude and knowledge, which is consistent with previous studies showing the importance of education in caregivers [7,21]. But Nzooma et al [11] in Zambia reported that higher levels of education were not related to higher knowledge levels and good practices towards malaria control. Our ndings indicated that the student mothers might know more but do less.…”
Section: Correlation Between Caregivers' Socio-demographic Characterisupporting
confidence: 86%
See 1 more Smart Citation
“…Meanwhile, having at least secondary level of education was found associated with a positive in uence on malaria related attitude and knowledge, which is consistent with previous studies showing the importance of education in caregivers [7,21]. But Nzooma et al [11] in Zambia reported that higher levels of education were not related to higher knowledge levels and good practices towards malaria control. Our ndings indicated that the student mothers might know more but do less.…”
Section: Correlation Between Caregivers' Socio-demographic Characterisupporting
confidence: 86%
“…Researches [7][8][9][10] concerning individual knowledge, attitudes and practices (KAPs) have shown that factors, including education levels, in some instances, are related to behaviour in malaria prevention and control. Behaviour is an important component in malaria prevention and control, but the behavioral status against malaria affected by the KAPs levels in the community was even more crucial [11].…”
mentioning
confidence: 99%
“…Misconceptions about causes of malaria in this study although reported by few respondents include living in dirty environment, eating contaminated food, stress, and exposure to sunlight. Some studies in Nigeria and parts of Africa have also reported spurious causes of malaria such as staying for long in the sun and drinking bad water among other misconceptions on malaria [ 11 , 21 , 23 , 24 ]. Overlapping knowledge on malaria causes, key symptoms, and prevention was observed between pregnant women and the non-pregnant mothers of children aged under 5 years in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Good malaria knowledge was associated with higher level of educational status of the women. In previous studies, educational status has been linked with good health awareness and health-seeking behaviour for the child [ 23 , 25 ], and also improved knowledge on malaria and prevention among mothers [ 9 , 18 , 26 ]. Such association according to Fana et al stresses the role education could have on the overall success in malaria control programmers in a region [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the respondents also associated mosquito bites with malaria transmission, in Zambia (Africa) [ 23 ], Swaziland (Africa) [ 16 ], in Muleba (Africa) [ 18 ]. This leads us to believe that the problem lies not in what populations know about malaria, but in the disconnection between them and the disease control plans taught by Departments of Health and other government entities [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%